Komunikasyon sa akademikong Filipino (Filipino 1) - Ronda, Lourdes A. (Metro Manila : Grandbooks, 2012)
Includes bibliography.
Keywords: Filipino language -- Readers and speakers; Filipino language -- Grammar; Filipino language -- Study and teaching